National Economics - Hughes, James H. (Journal of Reviews on Global Economics, 2014)
With the slow recovery from the Global Economic Recession that began in 2008 and its lingering high unemployment in the United States and Europe, in spite of the best efforts of governments and central banks to remedy it, it may be helpful to suggest some adjustments in current economic thinking. One adjustment may be found in the introduction of National Economics, in addition to macro and micro-economic theory, to better engage issues of free trade, the international outsourcing of manufacturing and research and development known as globalization, protectionism, Chinese mercantilism, and national investment policies, which may accompany the preparation of economic stimulus packages. While free trade is generally acknowledged as a positive factor in contributing to economic growth, it has been used by mercantilists, both countries and corporations, as a cloak to achieve a National Income redistribution to enrich themselves at the expense of reducing employment, and wages and salaries within a country, and to substitute poorly made or low quality goods for goods of better quality. One issue of National Economics that stands to be addressed is the contribution of Chinese mercantilism to the Global Economic Recession and its effect on unemployment rates. A major trading partner with the United States, Europe, and other countries, China uses a substantially undervalued currency compared to the U.S. dollar to increase its export of manufactured goods and economic growth rate, while suppressing the manufacturing sector in its trading partners. Within many countries, large trade imbalances with China play a role in the distribution of National Income by depressing employment, wages, salaries, and investment. While mercantilists claim that these reductions in employment, wages, and salaries are offset by the proliferation of inexpensive Chinese goods, low quality goods do not compensate for reductions in employment and investment. A second issue of National Economics that stands to be addressed, at least within the United States, is the need to prepare economic stimulus packages that represent a balance of new spending along with adjustments in entitlement programs and a reworking of the current regulatory environment, which policymakers use to reward corporate dinosaurs and financial manipulators, while the constrict the ability of small banks and lending institutions such as credit unions to make consumer loans and finance mortgages, with the effect of repressing the nation’s economy. Finally, some thoughts are given regarding the effect of Chinese mercantilism on Taiwan’s economy, and Japan’s effort to renew its economy.